An analysis of the third year english students` ability of fkip bung hatta university to write A cause and effect essay - Rahmi Amiladini; Lisa Tavriyanti; Yandri Yandri (International Journal of Educational Dynamics, 2020)
This research has attempted to describe the ability of the third year English students` ability of FKIP Bung Hatta University to write a cause and effect essay. The design of this research was descriptive. The numbers of population of this research were 122 students. The writer used cluster random sampling technique to determine the sample since the students were separated into four classes (A, B, C, and D). The writer chose one class as a sample of this research. Class B was decided to be the sample of this research. The numbers of this class were 20 students. The writer used writing essay test to collect data. Generally, the result of data analyzing the data showed that the ability of FKIP Bung Hatta University of the third year English students to write a cause and effect essay was moderate. It could be seen that 20% students had high ability, 70% had moderate ability, and 10% had low ability. Finally, based on the result above, the writer suggests the teachers to give more knowledge, explanation, practice in order to help students to improve their ability to write cause and effect essay. And students should do a lot of practices in order to improve their ability to write cause and effect essay.